2020
DOI: 10.3389/fneur.2020.00965
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage High-Density Focal Stereo-Array SEEG-Guided Radiofrequency Thermocoagulation for the Treatment of Pediatric Giant Hypothalamic Hamartomas

Abstract: Background: Giant hypothalamic hamartomas (HHs) are extremely rare lesions, for which the treatment is challenging. While minimally invasive treatments such as radiofrequency thermal coagulation and laser ablation have improved seizure outcomes, multiple operations are often required. This study investigated the value of one-stage stereo-array radiofrequency thermocoagulation based on stereotactic electroencephalography (SEEG) for pediatric giant HHs. Methods: We analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A patient from the study by Du et al 29 was excluded because of the absence of seizures at HH presentation. Finally, 15 studies 10,16,17,[26][27][28][29][30][31][32][33][34][35][36][37] enter the study. The study selection flowchart is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A patient from the study by Du et al 29 was excluded because of the absence of seizures at HH presentation. Finally, 15 studies 10,16,17,[26][27][28][29][30][31][32][33][34][35][36][37] enter the study. The study selection flowchart is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to craniotomy, Gamma Knife surgery has also exhibited a certain degree of efficacy for refractory epilepsy caused by HH (10). Recently, HH therapy has reached a new stage with the growth of the epileptic network theory and minimally invasive techniques such as stereoelectroencephalography (SEEG), radiofrequency thermocoagulation (RF-TC) (11,12), and magnetic resonance imaging (MRI)-guided laser interstitial thermal therapy (MRg-LiTT) (13)(14)(15). Many institutions, including Xuanwu Hospital of Capital Medical University, have conducted in-depth research on HH (1,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…A large-sampled prospective study reported a seizure-free rate of 7% and responder rate (defined as >50% decreased seizure frequency) of 48% at 1 year follow-up with permanent and transient side effect rates of 1.1 and 2.4%, respectively ( Bourdillon et al, 2017 ). The therapeutic effects of SEEG-guided RFTC in new specific indications have increasingly been identified, including hypothalamic hamartomas and periventricular nodular heterotopia ( Mirandola et al, 2017 ; Wei et al, 2018 ; Wang et al, 2020 ). And SEEG-guided RFTC has also been proven to be effective in treating insular epilepsy and malformation of cortical development (MCD)-related epilepsy ( Catenoix et al, 2015 ; Mullatti et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%